Management of Severe Cerebral Venous Sinus Thrombosis Using Mechanical Balloon Assisted Thrombectomy - Anand Alwan; Angel T Miraclin; Deepti Bal; Vinu Moses; Pavithra Mannam; Munawwar Ahmed; Santhosh Babu K.B; Kumar Muthukumar; Anitha Jasper; Sunithi Elizabeth Mani; Shalini Nair; Appaswamy Thirumal Prabhakar; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background Cerebral venous thrombosis is a devastating condition with, despite optimal medical management, a significant proportion deteriorating due to involvement of the deep venous system, worsening intracranial pressures, and hemorrhage. In this study, we report the characteristics, immediate and long‐term outcomes of mechanical thrombectomy (MT) using a Forgarty balloon catheter among patients with cerebral venous thrombosis. Methods A prospective study conducted at the Christian Medical College, Vellore over 5 years (February 2017–February 2022), wherein patients with cerebral venous thrombosis who had clinical deterioration despite best medical management and requiring MT were included. MT was performed through retrograde venous access through internal jugular veins using a Fogarty balloon. The primary outcome was composite end point of mortality and proportion of patients with favorable clinical response at last follow‐up, defined as a disability score in modified Rankin scale 0–2. Results Among 546 patients treated in our center during the study period, 57(10%), patients required MT. The median age of the study population was 33 years (interquartile range: 17–70 years) with equal gender predilection. Hemorrhagic venous infarction was seen in 28/57 (50%) patients. The mean duration between starting medical treatment and to MT was 43 hours (interquartile range: 5–260 hours) with the most common indication being clinical deterioration (70%). Five patients (9%) required decompressive hemicraniectomy. The mortality at discharge was 5% (n=3), and at last follow‐up visit was 7% (n=4). Younger patients without hemorrhagic venous infarction and non‐involvement of the frontoparietal lobes seem to benefit the most. Favorable functional outcome at discharge (modified Rankin scale 0–2) was seen in 65% which further improved to 77% at 1‐year follow‐up. Conclusion Balloon‐assisted MT is safe and effective in a subset of patients with severe cerebral venous thrombosis, with clinical deterioration despite optimal medical management.